Histological assessment of liver and stomach damage caused by pyridazinone derivative antidepressant agents - Ozdemir, Zeynep; Karakurt, Arzu; Taslidere, Elif; Vardi, Nigar; Alagoz, Mehmet Abdullah; Parlakpinar, Hakan; Bag, Harika Gozukara (Taylor & Francis Ltd, 2022)
Depression is a serious psychological disorder that affects a significant population. We investigated the antidepressant activities of four pyridazinone derivatives that contain the hydrazide moiety using the forced swimming test (FST). The compounds tested exhibited good antidepressant activity compared to duloxetine. The most promising compound was compound 2, which reduced the duration of immobility during FST. The toxic effects of the four compounds on the histomorphology of the liver and stomach tissue also was evaluated.
Keywords: Antidepressant; histopathology; liver; mice; pyridazinone; stomach; swimming test